Adaptasi Pasien HIV/AIDS Selama Pengobatan Antiretroviral (ARV) - Supriatun, Evi; Hasni, Nafisah Itsna; Marsono, Marsono (Journal of Telenursing (JOTING), 2024)
This study aims to find out experiences related to the adaptation process of HIV/AIDS patients during antiretroviral (ARV) treatment. This study uses a qualitative method. with a phenomenological design, with in-depth interviews with 10 participants with HIV/AIDS who are undergoing ARV therapy. The results of the study found 3 (three) main themes related to self-acceptance, behavioral transformation that supports health and mental strengthening in the adaptation experience of HIV/AIDS patients. From this study, it was concluded that the adaptation the process of HIV/AIDS patients starts from emotional experiences after being diagnosed with HIV/AIDS, to finally strengthening mentally as a challenge in undergoing ARV treatment to maintain their lives. Keywords: Adaptation, ARV Treatment, HIV/AIDS